2015
DOI: 10.1152/japplphysiol.00857.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleeping with reduced carbohydrate availability on acute training responses

Abstract: We determined the effects of "periodized nutrition" on skeletal muscle and whole body responses to a bout of prolonged exercise the following morning. Seven cyclists completed two trials receiving isoenergetic diets differing in the timing of ingestion: they consumed either 8 g/kg body mass (BM) of carbohydrate (CHO) before undertaking an evening session of high-intensity training (HIT) and slept without eating (FASTED), or consumed 4 g/kg BM of CHO before HIT, then 4 g/kg BM of CHO before sleeping (FED). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 36 publications
7
120
2
1
Order By: Relevance
“…At present, research studies examining the efficacy of train-low strategies have largely adopted fasted training protocols [60], protein only sessions [70], training twice per day models [62] reducing CHO intake in the post-exercise period [71] and most recently, both sleeping and training (i.e. sleep low-train low models) on the subsequent morning with reduced CHO intake [21,72]. Ultimately, the simplest advice at present may be to adopt the practical concept of "fuelling for the work required" in that completing pre-determined training workloads that can be readily performed with reduced muscle glycogen and without exogenous CHO feeding may represent a strategic approach for which to implement day-today nutrient-exercise periodization protocols.…”
Section: Is Carbohydrate Still King?mentioning
confidence: 99%
“…At present, research studies examining the efficacy of train-low strategies have largely adopted fasted training protocols [60], protein only sessions [70], training twice per day models [62] reducing CHO intake in the post-exercise period [71] and most recently, both sleeping and training (i.e. sleep low-train low models) on the subsequent morning with reduced CHO intake [21,72]. Ultimately, the simplest advice at present may be to adopt the practical concept of "fuelling for the work required" in that completing pre-determined training workloads that can be readily performed with reduced muscle glycogen and without exogenous CHO feeding may represent a strategic approach for which to implement day-today nutrient-exercise periodization protocols.…”
Section: Is Carbohydrate Still King?mentioning
confidence: 99%
“…This has led to interest in a “periodized” approach to CHO availability in the training program, where sessions undertaken to promote adaptation are carefully integrated with others focused on high quality performance outcomes. The “sleep-low” (SL) strategy represents one such sequence of periodized CHO availability, which allows athletes to perform high intensity training sessions supported by high CHO availability while enhancing metabolic adaptation associated with low glycogen availability [14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that this strategy leads to increased activity of several proteins with putative roles in training adaptation (AMPK, p38 MAPK, p53) [9,14] and higher rates of fat oxidation during submaximal exercise [14]. However, the effects on endurance performance are equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent study in skeletal muscle, demonstrated acute metabolic stress (aerobic exercise) reduces DNA methylation of enhancer regions (hypomethlyation) of genes associated with mitochondrial biogenesis (PGC-1α, PDK4 and PPAR-δ) that presumably in turn allowed increased promoter activity (although not directly investigated) and thus increased corresponding transcript expression (Barres et al 2012). Similarly a more recent study suggests that acute nutritional manipulation (fasting) in combination with acute exercise also provides evidence of an inverse relationship with DNA methylation and gene expression of important metabolic genes involved in substrate utilization (Lane et al 2015). However, adaptation in the terms of stable methylation patters after chronic anabolic exercise stimuli or periods of catabolic injury/disuse remains unstudied, as do methylation of genes that control muscle mass.…”
Section: Discussionmentioning
confidence: 99%